Impact of planting dates on yield and pod quality traits of snap bean under short-temperate season climates - Rao, S. (International Journal of Horticultural Science, 2022)
Snap bean, a warm-season crop, have low frost tolerance. The optimal temperature for seed emergence and plant growth is important. Therefore, appropriate planting dates for adapted varieties has paramount significance in improving pod yield and quality of snap bean under short cool season climates. Three snap bean cultivars planted at 3 different dates were examined to evaluate the effects of planting dates on snap bean pod yield and quality traits in a 2-year study in a short season climate in Manitoba, Canada. Results of this study showed that three, two weeks apart, planting dates had a non- significant effect on marketing yield of three different cultivars tested in this study. Planting dates showed significant effect on un-marketable yield, pod fresh weight, pod length and total soluble solids. Higher marketable and un-marketable yields along with longer pod length and soluble solids, in all three cultivars, were more profound when seeded at mid and late planting dates. Snap bean grew under higher temperature and accumulated more growing degree days (GDD) when planted in mid June and early July when compared to early June planting. These results conclude that marketable yields of snap bean were not significantly affected by planting dates when seeded-two weeks apart-in shorter growing environments which allow commercial and market gardeners, in northern areas with shorter growing seasons to optimise planting snap bean, without reducing pod yield and quality.